Examining Code-Switching in the Cindy Kaza and Mongol Stress Episode of Diary Misteri Sara - Zehar, Rafika; Humaniika, Eko Setyo; Dewi, Septi Riana; Radjaban, Yohanes; Matas, Gordan (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2025)
This study aims to analyze code-switching in an episode of Diary Misteri Sara, a program featured on Sara Wijayanto’s YouTube channel, specifically the episode involving Cindy Kaza and Mongol Stress. The primary objective is to identify the types and functions of code-switching present in the interactions between the Diary Misteri Sara team and their collaborators. Employing a qualitative approach, the analysis draws on Stockwell’s classification of code-switching types and Gumperz’s framework for its functions. A total of 218 instances of code-switching were identified, comprising tag switching (24 instances, 10.55%), inter-sentential switching (41 instances, 18.81%), and intra-sentential switching (154 instances, 70.64%). In terms of function, six categories were found: quotation (2 instances, 0.92%), addressee specification (32 instances, 14.68%), interjection (23 instances, 10.55%), reiteration (22 instances, 10.09%), message qualification (26 instances, 11.93%), and personalization versus objectification (113 instances, 51.83%). The results indicate that intra-sentential switching is the most frequently used type, while personalization versus objectification is the most dominant function. These findings contribute to a deeper understanding of the patterns and communicative roles of code-switching in multilingual interactions within digital media contexts.